2016
DOI: 10.1159/000445361
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-PLA<sub>2</sub>R Antibody Predicts Treatment Outcome in Idiopathic Membranous Nephropathy

Abstract: Background: M-type phospholipase A2 receptor (PLA2R) has been identified as the major target antigen in idiopathic membranous nephropathy (IMN). However, the role of glomerular PLA2R (gPLA2R) and the associations of serum anti-PLA2R antibody (sPLA2R-Ab) titre with diagnosis, treatment and prognosis in IMN need to be further investigated. Methods: We screened 148 consecutive patients with biopsy-proven membranous nephropathy (MN; 113 with IMN and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 28 publications
4
44
1
Order By: Relevance
“…The clinical sensitivity of the ChLIA exceeded that of ELISA and RC-IFA by 10.4% and 0.7%, respectively, at similar specificities (>99%). The anti-PLA2R-positive rates detected by ChLIA (83.9%), ELISA (73.5%), and RC-IFA (83.2%) were equal to or higher than the prevalence data determined among non-preselected patients with pMN by different methods, such as Western blot (53.0%-81.7%), 10,11 RC-IFA (48.0-82.3%), 12,13 ELISA (50.0-71.8%), 14,15 addressable laser bead immunoassay (51.5-66.9%), 16,17 luciferase immunoprecipitation systems assay (53.3%), 18 and time-resolved fluoroimmunoassay (71.0-89.7%). 19,20 These variations may be due to differences in assay techniques (e.g., epitope exposure, cutoff values, detected Ig subclass) and cohort characteristics (e.g., ethnicity, immunosuppressive treatment).…”
Section: Discussionmentioning
confidence: 69%
“…The clinical sensitivity of the ChLIA exceeded that of ELISA and RC-IFA by 10.4% and 0.7%, respectively, at similar specificities (>99%). The anti-PLA2R-positive rates detected by ChLIA (83.9%), ELISA (73.5%), and RC-IFA (83.2%) were equal to or higher than the prevalence data determined among non-preselected patients with pMN by different methods, such as Western blot (53.0%-81.7%), 10,11 RC-IFA (48.0-82.3%), 12,13 ELISA (50.0-71.8%), 14,15 addressable laser bead immunoassay (51.5-66.9%), 16,17 luciferase immunoprecipitation systems assay (53.3%), 18 and time-resolved fluoroimmunoassay (71.0-89.7%). 19,20 These variations may be due to differences in assay techniques (e.g., epitope exposure, cutoff values, detected Ig subclass) and cohort characteristics (e.g., ethnicity, immunosuppressive treatment).…”
Section: Discussionmentioning
confidence: 69%
“…Although some studies found an association between the degree of proteinuria and PLA2R Ab titer at a defined time point, 30,33,39,40 others found only a weak or no association. 13,22,41 Such variability in association likely reflects the time lag between immunologic and clinical activity, and indeed, a latency period as long as 8 months has been observed between the presence of PLA2R Ab in serum and the first clinical manifestations of MN.…”
Section: Prognostic Value Of Pla2r Abmentioning
confidence: 97%
“…Others studies found small numbers of positive patients in various groups of secondary MN. 15,[27][28][29][30][31][32][33] The question thus arises whether these patients represent true secondary MN or rather, PLA2R-associated MN with coincident secondary disease. The latter possibility is supported by the following findings in such studies.…”
Section: Diagnostic Value Of Pla2r Abmentioning
confidence: 99%
“…Newly discovered autoantigens, such as PLA2R [7] and THSD7A [8] , and complement system activation have been found to be involved in the pathogenesis of MN [9] , providing us with a better understanding of the causes of IMN. However, the effects of IMN treatment differ substantially, and many researchers are constantly seeking biological indicators for the disease status and prognosis of IMN.…”
Section: Discussionmentioning
confidence: 99%